DICER1 hot‐spot mutations in ovarian gynandroblastoma. Issue 2 (5th June 2018) - Wang, Yemin; Karnezis, Anthony N; Magrill, Jamie; Tessier‐Cloutier, Basile; Lum, Amy; Senz, Janine; Gilks, C Blake; McCluggage, W Glenn; Huntsman, David G; Kommoss, Friedrich
Abstract : Aims: Gynandroblastoma is a rare ovarian sex cord‐stromal tumour characterised by the presence of both male (Sertoli and/or Leydig cells) and female (granulosa cells) components. We investigated the mutational status of DICER1, FOXL2 and AKT1 genes at hot‐spot regions that are known to be the key driving events in the development of Sertoli–Leydig cell tumour (SLCT), adult granulosa cell tumour (aGCT) and juvenile granulosa cell tumour (jGCT), respectively, to gain insights into the molecular pathogenesis of gynandroblastoma. Methods and results: Sixteen cases of gynandroblastoma were studied. All contained SLCT or Sertoli cell tumour components. aGCT and jGCT components were identified in seven and 10 cases, respectively, with one presenting both components. Heterozygous hot‐spot mutations in the RNase IIIb domain of DICER1 were discovered in three cases, including one case with heterologous mucinous elements, all of which were composed of moderately or poorly differentiated SLCT and jGCT components, and harboured the mutations in both histological components. None of the 16 cases displayed mutations at the p.C134W ( c.402C→G ) of FOXL2 or within the pleckstrin‐homology domain of AKT1 . All cases showed FOXL2 immunostaining in both male and female components. Conclusion: DICER1 hot‐spot mutation is the key‐driving event in a subset of gynandroblastomas containing components of SLCT and jGCT. Gynandroblastomas composed of SLCT and jGCT may represent morphological variants of SLCT. The molecular basis of gynandroblastoma containing a component of aGCT is different from pure aGCT.